The Hardships of Long Distance Relationships: Time Zone Proximity and Knowledge Transmission within Multinational Firms - Dany Bahar (Institute of Labor Economics (IZA), 2018)
Using a unique dataset on worldwide multinational corporations with precise location of headquarters and affiliates, I present evidence of a trade-off between distance to the headquarters and the knowledge intensity of the foreign subsidiary's economic activity, emerging from dynamics related to the proximity-concentration hypothesis. This trade-off is strongly diminished the higher the overlap in working hours between the headquarters and its foreign subsidiary. In order to rule out biases arising from confounding factors, I implement a regression discontinuity framework to show that the economic activity of a foreign subsidiary located just across the time zone line that increases the overlap in working hours with its headquarters is, on average, about one percent higher in the knowledge intensity scale. I find no evidence of the knowledge intensity and distance trade-off weakening when a non-stop flight exists between the headquarters and the foreign subsidiary. The findings suggest that lower barriers to real-time communication within the multinational corporation play an important role in the location strategies of multinational corporations.
Keywords: F23; L22; L25; 330; multinational firms; multinational corporations; knowledge; location; proximity concentration hypothesis; FDI